KEBIJAKAN PENGUASA JAWA KUNO: BALITUNG DALAM SEBUAH KAJIAN EPIGRAFI - Listyanto Aji Nugroho; Emy Wuryani; Sunardi Sunardi (Cakrawala Jurnal Penelitian Sosial, 2018)
Balitung, the ruler of ancient java. He can be the role model of true leader in modern era. From his era, we can study about how the leader leading something. Nowadays, people get much news about a court session on television. People eventually have shocked with the judgment resolution that doesn’t appropriate with justice. On Ancient Java era, the court session had occurred. That court session usually about dispute side by side. Learning about court mechanism on the past is a part of studying history. With studying history, people can use past event as education with comparing past event with present. Although, this research also held to find out about tax amnesty program on Balitung’s era. To find out about the topics, a historiographical research was held with epigraphy approach that using inscription as the main topics. This research consists of four stages: (1) heuristic, (2) verification, (3) interpretation, (4) writing. From this research it’s known that a court session was led by the lord of the state as a judge. To find out the truth, the judge held evidentiary mechanism called triprangama, consists of sakshi, likhita, and bhukti. After evidentiary process, everyone who can show the truth will win the court. An then, in order to get a tax amnesty the folk can apply for it to Rakryan Mahamantri I Hino (King Balitung Crown prince) to get an approval from King Balitung.